In-situ surface modification and bulk alloying of anti-bacterial Cu-bearing stainless steel using selective laser melting - Liu Kun; Ioi Lei Wang; Lap Mou Tam; Kin Ho Lo; Ruidi Li; Chi Wai Chan; Valentino A.M. Cristino; Chi Tat Kwok (Materials & Design)
The development of alloys for biomedical applications with antibacterial properties requires a delicate balance of the materials’ mechanical, corrosion and antibacterial properties, its cost effectiveness, fabrication precision and ease for tailor-made components. In this study, Cu-bearing stainless steel Fe-Cr-Ni-Cu with different Cu contents (4 and 8 wt%) were prepared by surface modification and bulk alloying using selective laser melting (SLM) and their microstructure, metallurgical properties, hardness, corrosion resistance and antibacterial efficacy were evaluated. The results indicated that the SLMed Fe-Cr-Ni-Cu alloy obtained from both methods exhibits similar properties, with the increase of Cu content led to a minor reduction in hardness and worsening its corrosion resistance. The improved antibacterial efficacy (up to 98.5 %) of the SLMed Fe-Cr-Ni-Cu alloy are originated by the formation of the ε-Cu phase and the alterations in the oxide-to-metal ratio in the composition of the passive film, compromising its integrity, resulting in an active shift in pitting potential and a constant release of Cu+ ions.